The Effect of Work Discipline and Job Performance on Job Promotion at PT. Daya Sakti Perkasa In Tangerang - Zacharia Rialmi; Lia Asmalah (PINISI Discretion Review, 2020)
Leaders must realize the importance of promotion in increasing productivity which must be considered objectively. The purpose of this study was to determine the effect of work discipline and work performance on job promotions at PT. Daya Sakti Perkasa in Tangerang. The method used in this research is descriptive with an associative approach, the sampling technique used is proportional random sampling using the census or saturated sampling method with a sample of 78 respondents. The analysis tool uses instrument testing, classical assumption testing, regression testing, determination coefficient testing and hypothesis testing. The results of the study concluded that there was a positive and significant effect both partially and simultaneously between work discipline and work performance on promotion with a contribution of 0.576 or 57.6% while the remaining 42.4% was influenced by other factors. Hypothesis testing is obtained F count> F table (50.850> 2.730) thus H0 is rejected and H3 is accepted meaning that there is a positive and significant effect simultaneously between work discipline and work performance on job promotions at PT. Daya Sakti Perkasa in Tangerang.